Medico-legal Aspect of Abruptio Placentae: A Case Report (Indian Internet Journal of Forensic Medicine and Toxicology, 2017)
Obstetric haemorrhage is one of the major causes of maternal death in developing countries. The term obstetric haemorrhage encompasses both antepartum and post-partum haemorrhage. Placental abruption is known to be a significant cause behind both antepartum and post-partum bleeding. Abruption is often an unanticipated emergency and a small bleed can suddenly evolve into a major abruption. Therefore, vigilance is very essential. Placental abruption often happens suddenly. Left untreated, placental abruption can lead to significant maternal and foetal morbidity and, ultimately, maternal and foetal death. Current understanding of coagulopathies and replacement of clotting factors along with increasing confidence in uterotonic agents have reduced the necessity to remove the couvelaire uterus to rare circumstances. But, the obstetric haemorrhage that remains unresponsive to medical and conservative management must be treated with hysterectomy sooner than later. The decision to proceed with a hysterectomy should take into account several factors. Obviously, mother’s life is of paramount concern. It should be judged taking into account maternal safety, the urgency of situation, likelihood of success with other options and desires of a patient to have additional children. A case has been filed before the Gujarat State Consumer Dispute Redressal Commission on the issue of ‘abruptio placentae’ and finds doctor negligent and awarded compensation. Aggrieved doctor filed appeal before National Consumer Dispute Redressal Commission, New Delhi who found merit in the appeal and set aside the order of Gujarat, State Consumer Disputes Redressal Commission (SCDRC). The court finally found the doctor not guilty; however, various medico-legal issues related to duty of doctors, role of informed consent, need for referral, standard of practise and others have been discussed to clarify why there is no medical negligence in this case.
Keywords: Abruptio placentae; Medical record; IUD; Consent; LSCS; Hysterectomy